GaN-based high-periodicity multiple quantum well solar cells: Degradation under optical and electrical stress. (November 2020) - Caria, A.; De Santi, C.; Zamperetti, F.; Huang, X.; Fu, H.; Chen, H.; Zhao, Y.; Neviani, A.; Meneghesso, G.; Zanoni, E.; Meneghini, M.
Abstract: We investigate the degradation of InGaN-GaN MQW solar cells under optical and electrical stress. We submitted the devices to high temperature, high optical power stress and we found that, under optical stress, the devices show a moderate decrease in open-circuit voltage, possibly due to creation of defect-related shunt paths. This degradation is partially recovered after room temperature storage. The stronger decrease of open-circuit voltage under electrical stress at high current suggests a role of carrier flow in the degradation. Highlights: Reliability of GaN-InGaN multiple quantum well solar cells has been investigated. Devices have been submitted to optical, temperature and current stresses. Devices showed a decrease in open-circuit voltage and power conversion efficiency. The degradation is partially recovered after 52 days of storage in air at 25 °C. Degradation has been related to the creation of metastable defects.